The Effect of Innovation through R&D Expenditure on the Competitive Performance of Firms - Al Mobayed, Aliaa (2012)
Strategic management research has identified several determinants of competitive advantage one of which is innovation. Accordingly, managers and policy makers introduced various schemes to justify R&D expenditures in firms and encourage the adoption of innovative products and processes across numerous industries. This study sheds light on the impact of innovation on the competitive performance of firms and investigates the volatility of this innovation-induced performance. This is achieved by quantitatively measuring the effect of R&D expenditures on the profitability and growth rates of innovating firms from four R&D-intensive industries namely pharmaceutical, chemical, electrical and semi-conductor. The results reported indicate a significantly positive impact of R&D expenditure on the profitability and growth of firms which is consistent with previous studies on the topic. In addition to R&D expenditure, this research identifies other variables that significantly affect competitive performance such as advertising expenditure and firm size. The findings also highlight the volatility of firm performance across different industries and time periods. These results support the theory of temporary competitive advantage which suggests that the competitive performance resulting from R&D expenditure is temporary rather than sustainable in the long-term. The strategic implications of this study’s findings indicate that continuous investment in R&D and innovation activity is necessary for a firm to sustain its competitive advantage. Additionally, a company has to integrate innovation into its holistic management strategy to enhance efficiency and productivity throughout the organisation. Finally, further research on this topic is necessary in order to devise a more precise model for measuring competitive performance that could incur significant benefits on business strategy and firm performance.